Modification of hurling helmets causing penetrating upper limb injury: A case series demonstrating opportunity for improved player safety. Issue 2 (April 2022) - Quinlan, Christine S.; Farrell, Tony; Joyce, Cormac W.; Kelly, Jason; O'Sullivan, Sean T.; O'Sullivan, J. Barry
Abstract: Background: The games of hurling and camogie involve fast ball movement and a substantial physical contact with opposing players. The wearing of protective helmets with faceguards became obligatory 10 years ago and resulted in a significant reduction of craniofacial injuries. However since then a trend has emerged of players modifying helmets to improve comfort and vision. As officials are not yet required to perform pre-match checks, many players enter competition with defective protective equipment which poses a risk to both themselves and others. Methods: We present 4 cases of penetrating upper limb injury in hurlers sustained as a result of helmet faceguards. These injuries were sustained during competitive play and the affected patients presented with portions of the faceguards embedded in their wounds. Each patient required admission to hospital and exploration of their wounds under general anaesthetic. Conclusions: This case series demonstrates the dangers of modification and damage to protective helmet faceguards used in hurling and camogie. We encourage helmet manufacturers to re-engage with players to ensure that current safety equipment meets the functional demands of the modern player while adhering to approved manufacturing standards. Mandatory helmet checks before competitive games would reduce the likelihood of penetrating upper limb injury to players. Highlights: Four cases of penetrating upper limb injury from hurling helmets are presented. The cases demonstrate the danger of modification to hurling helmets and faceguards. Helmet design should meet player demands and adhere to manufacturing standards.